PENGARUH QUALITY OF WORK LIFE DAN KOMITMEN GURU TERHADAP KINERJA GURU DENGAN MEDIASI KEPUASAN KERJA PADA SMP RSBI DI KABUPATEN PEKALONGAN - Asmujiono, Tri (Students Journal of Economic and Management, 2012)
This research aims to analyze the role of the Quality Of Work Life and Teachers Commitment Mediation Effect of Job Satisfaction of Performance state junior high school Teachers of SMP RSBI Pekalongan Regency. In this research population of 102 people, while the sample was taken as many as 88 people as respondents with a purposive sampling method. With all of the criteria of SMP RSBI of Pekalongan RegencyBased on the results of the research can be summarized as follows: (i) Quality of Work Life has a positive and significant impact  of Job Satisfaction , (ii)Quality Of Work Life  a negative and does not significant impact of Teacher Performance, (iii) Teacher Commitment have a negative and does not significant impact onjob Satisfication , (iv) Teacher Commitment has positive and significant impact of Teacher performance, (v) Job Satisfication has negative and does not significant ofr Teacher performance (vi) Job Satisfication did not mediation of Quality Of Work Life is Quality Of Work Life and Teacher Commitment  for Teacher Performance. Keywords: Quality Of Work Life ,Teacher Commitment Job Satisfaction and Teacher  Performance.